ELECTRONIC PAYMENT FOR BILLS: CONTROLS AND PROVISIONS AN EMPIRICAL STUDY - Adel Abdel Fadil Eid Bleek, Nasser Rady Al-Zuhri Ibrahim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Trade exchange between banks, financial cards, credit cards, credit cards, credit cards, cards, cards, cards, financial cards, financial cards, and mobile companies, in addition to the online portal and its application, or through outlets, branches and service points Using electronic money. And in return for the company’s commission, the client is obligated to pay it, whether it is an individual or an institution. This research aims to understand the concept of electronic payment, its types, fields, and jurisprudential rulings, in addition to setting controls for electronic payment from the forbidden Sharia, to be electronic starting points for electronic and Sharia instructions. This research was organized in an introduction and consistency of discussions and a conclusion that included the most important findings and recommendations, including: The electronic payment systems for bills can be adapted and downloaded to types of contracts in Islamic jurisprudence, such as Churning out, transfer and leasing. They represent a good alternative to old payment methods, and are characterized by ease and convenience, saving effort and money, and speed of completion. The basic principle is that dealing with electronic payment systems is legally permissible, and each card or system has its own legal controls. Failure to comply with the provisions of Islamic law is one of the most important causes of economic crises and fluctuations. Islamic financial institutions must search for alternatives to uncovered electronic payment cards, and adhere to their issuance and terms of Sharia controls. Urging the competent authorities to issue regulations and regulations that enable the use of modern technology, keep abreast of progress, provide security and confidence in dealing, and solve problems in the field of e-commerce. Benefiting from competencies and successful experiences by exchanging experiences between electronic financial institutions. Spreading awareness about the jurisprudence of electronic financial transactions to know the rights and duties and avoid falling into problems and discounts.